Determinants of Categories of TB Retreatment with Special Reference to Sources of Primary Anti-TB Treatment - Karthikeyan, Veerabadran; Ganapathy, Kalaiselvan (Journal of Health and Allied Sciences NU, 2020)
Introduction Retreatment (previously treated) cases are the tuberculosis (TB) patients who have been treated previously with anti-TB drugs for at least a month and who have now been registered for category II anti-TB therapy. Retreatment cases arise due to inadequate and improper treatment of the new TB cases.Objective The aim of the study is to assess the information regarding sources of previous TB drug exposure and treatment practices leading to retreatment cases (category II) and determinants leading to retreatment.Material and Methods It was a community-based cross-sectional study of patients registered as retreatment TB cases under revised national TB control program (RNTCP) in the TB unit of Puducherry between October 2013 and September 2014. The study was held between October 2013 and October 2015. Initially the quantitative data were collected and followed by qualitative data. Data were collected by interviewing the patients using a predesigned questionnaire. Data were entered and analyzed by using Epi Info (Version 3.4.3) software package.Results Out of the 193 study participants, relapse cases were the most common 50.8%, followed by treatment after default cases 23.8%, failure cases 11.9%, and retreatment others 13.5%. There is a significant association between the retreatment categories such as failure, TAD (treatment after default), retreatment others, and ever usage of tobacco (p < 0.05). There is also a significant association between the retreatment categories such as TAD, retreatment others, and ever usage of alcohol (p < 0.05). The sources of previous antitubercular therapy for 90.16% retreatment cases were from government health care facilities under RNTCP, whereas for 9.84% retreatment cases the sources of previous antitubercular treatment were private health care facilities. There is a significant association between public health care facility where patients were previously treated for TB and relapse (p = 0.001) and private health care facility where patients were previously treated for TB and TAD (p = 0.008).Conclusion As 90% of the patients have utilized the government health services for treatment, it shows the effective functioning of RNTCP-STF (state task force-revised national TB control program) mechanism in Puducherry.
Keywords: previously treated; retreatment; sources of previous treatment; tuberculosis